SISTEM KEARSIPAN ADMINISTRASI DESA BERBASIS WEB - Mokhamad Iklil Mustofa; Zaenal Mustofa (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Internet network infrastructure is currently very rapid and is followed by the movement / mobilization of the community in fulfilling the needs of life and education (temporarily domiciled outside the city), as well as public awareness of  the  needs  of  village  administrative  requirements,  such  as  family  cards, identity cards, birth certificates, ownership letters land and other village administrations, so that the village apparatus must be extra in carrying out data collection on the village in an integrated manner, so that it can be accessed anywhere via an internet connection without returning to their hometown. Villagers who migrate outside the island want to make birth certificates, renew e-ID cards, family cards, etc., do not need to go back to their hometowns, just send physical and file-scanned files that are expected to be applied "Village Administration Based Archive System Web "to request these documents. When there are villagers who sell and sell other than recorded in a notary can also be recorded, any transfer of administrative rights can be recorded in the village with this village archival system. All village data will be recorded / records relating to education, employment, birth certificate, e-ID card, ownership of land certificates, payment of land and building taxes, and other village administration requirements. Keywords: archival system, village administration, web, villagers, internet, data access